Childhood abuse and neglect, attachment states of mind, and non-suicidal self-injury. Issue 5 (3rd September 2017) - Martin, Jodi; Raby, K. Lee; Labella, Madelyn H.; Roisman, Glenn I.
ABSTRACT: This investigation examined preoccupied attachment states of mind as both a risk factor for non-suicidal self-injury (NSSI) and as a mechanism by which prospectively assessed childhood experiences of abuse and neglect predicted the frequency/severity of NSSI behavior up to age 26 years in 164 individuals (83 females) who were followed from birth in the Minnesota Longitudinal Study of Risk and Adaptation. Preoccupied (but not dismissing) states of mind regarding both childhood caregivers and adult romantic partners were correlated with more frequent/severe NSSI. Furthermore, preoccupied states of mind regarding caregivers partially accounted for the association between childhood abuse/neglect and NSSI. This work represents a rare prospective test of a developmental psychopathology framework for understanding NSSI behavior, in which atypical caregiving experiences are carried forward through attachment representations of caregivers that reflect behavioral risk.